Penerapan Perilaku Hidup Sehat Dalam Perawatan Kesehatan Gigi serta Mulut pada Siswa di SD Negeri 2 Telaga - Hulopi, Abdul Karim; Haryani, Meri; Saprin Kaawoaan, Ahmad Dzulfikar Ibnu Sibnu; Basiha, Djafar; Lakuntu, Jusriawan J; Abdul, Mohamad Isra; Manggopa, Nangsi; Rauf, Noval Pratama; Irawan, Safri (Universitas Negeri Gorontalo, 2025)
Dental and oral health is an important aspect of maintaining overall health, especially for school-age children. A lack of knowledge and improper habits in maintaining oral health often lead to issues such as cavities and gum disease. This activity aims to enhance students' understanding of the importance of maintaining dental and oral health, as well as providing education on healthy lifestyle behaviors that support optimal dental health. The activity took place on (date) at SD Negeri 2 Telaga, involving (number of) students. The program included delivering materials on dental and oral health, demonstrating the correct technique for brushing teeth, and conducting dental check-ups. The results of the activity showed that students were highly interested and enthusiastic about learning the importance of maintaining oral health. Additionally, some dental issues were identified and could be promptly addressed. The evaluation of the activity indicated an increase in students' understanding of healthy living behaviors, especially in maintaining dental and oral health. This activity had a positive impact on the students, and it is hoped that similar programs will be conducted regularly to improve dental and oral health among school-age children.